Iqbal’s philosophical views on the nature of man - Abdul Razak, Mohd Abbas; Laluddin, Hayatullah (CENTRIS, IIUM, 2024)
Human nature has drawn the interest of many concerned parties, including religious scholars, philosophers, biologists, psychologists, and others who continue to explore and discover the many hidden potentials within man. Many Western views on human nature are based on the ideas presented by Darwin and Freud. In contrast to the purely secular and scientific perspectives of the West, the concept of human nature in the Muslim world is rooted in the teachings enshrined in the Qur’an and Sunnah.